Molecular phylogeny of Anopheles hyrcanus group (Diptera: Culicidae) based on mtDNA COI - Yuan Fang; Wen-Qi Shi; Yi Zhang (BMC, 2017)
Abstract Background The Anopheles hyrcanus group, which includes at least 25 species, is widely distributed in the Oriental and Palearctic regions. Some group members have been incriminated as vectors of malaria and other mosquito-borne diseases. It is difficult to identify Hyrcanus Group members by morphological features. Thus, molecular phylogeny has been proposed as an important complementary method to traditional morphological taxonomy. Methods Based on the GenBank database and our original study data, we used 466 mitochondrial DNA COI sequences belonging to 18 species to reconstruct the molecular phylogeny of the Hyrcanus Group across its worldwide geographic range. Results The results are as follows. 1) The average conspecific K2P divergence was 0.008 (range 0.002-0.017), whereas sequence divergence between congroup species averaged 0.064 (range 0.026-0.108). 2) The topology of COI tree of the Hyrcanus Group was generally consistent with classical morphological taxonomy in terms of species classification, but disagreed in subgroup division. In the COI tree, the group was divided into at least three main clusters. The first cluster contained An. nimpe; the second was composed of the Nigerrimus Subgroup and An. argyropus; and the third cluster was comprised of the Lesteri Subgroup and other unassociated species. 3) Phylogenetic analysis of COI indicated that ancient hybridizations probably occurred among the three closely related species, An. sinensis, An. belenrae, and An. kleini. 4) The results supported An. paraliae as a probable synonym of An. lesteri, and it was possible that An. pseudopictus and An. hyrcanus were the same species, as evident from their extremely low interspecific genetic divergence (0.020 and 0.007, respectively) and their phylogenetic positions. Conclusions In summary, we reconstructed the molecular phylogeny and analysed genetic divergence of the Hyrcanus Group using mitochondrial COI sequences. Our results suggest that in the future of malaria surveillance, we should not only pay much attention to those known vectors of malaria, but also their closely related species.